PENGARUH PENGETAHUAN DEWAN TENTANG ANGGARAN TERHADAP PEGAWASAN KEUANGAN DAERAH DENGAN TRANSPARANSI KEBIJAKAN PUBLIK SEBAGAI VARIABEL MODERASI - Kristomar Yossia Poeras; Yohanes Joni Pambelum; M. Ichsan Diarsyad (Balance: Media Informasi Akuntansi dan Keuangan, 2022)
This study aims to test the influence of Board Members' Knowledge on Budget on Regional Financial Supervision, and also to test whether public policy transparency variables can strengthen the relationship.This research uses quantitative approach with moderation analysis using IBM SPSS Statistic Version 25.The data was obtained by surveying 45 members of the Central Kalimantan Provincial DPRD council. Data used in the study is primary data, data analysis using simple linear regression and moderation regression equation analysis ( Moderated Regression Analysis / MRA) The results of hypothetical test analysis show that there is a positive influence of The Board Member's Knowledge on Budget on Regional Financial Supervision.The results of the analysis with moderation variables show that the Public Policy Trasnparansi can strengthen the influence of The Board Member's Knowledge on The Budget on Regional Financial Supervision and these results are expected that Public Policy Transparency can contribute to any oversight carried out by board members